2004
DOI: 10.1063/1.1781751
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation in a polymer thin film induced by an in-plane electric field

Abstract: This letter reports experimental work involving use of an in-plane electric field to induce morphological patterns in a thin polymer film. The film was first spin coated onto a glass wafer. Then, it was heated to above its glass transition temperature to achieve mobility in the fluid. An in-plane electric field was applied using two parallel electrodes, spaced 10 mm apart, whereupon the initially flat polymer/air interface lost stability and formed islands. The self-assembled islands exhibited a narrow size di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…For example, various groups have used an electric field which is perpendicular (or normal) to an air/polymer interface (Deshpande et al 2004;Schaffer et al 2001), or a polymer/ polymer interface (Lin et al 2001), or an ionic liquid/ polymer interface (Lau and Russel 2011), or air/polymer/ polymer interfaces (Morariu et al 2003;Reddy et al 2012) to create micro-patterns. The interfacial stresses, however, can also be generated by a tangential electric field (Roberts 2009;Melcher 1974). Using an electric field parallel to an air/polystyrene interface, Salac et al (2004) obtained randomly distributed islands with different sizes on the surface of a polystyrene film.…”
Section: List Of Symbolsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, various groups have used an electric field which is perpendicular (or normal) to an air/polymer interface (Deshpande et al 2004;Schaffer et al 2001), or a polymer/ polymer interface (Lin et al 2001), or an ionic liquid/ polymer interface (Lau and Russel 2011), or air/polymer/ polymer interfaces (Morariu et al 2003;Reddy et al 2012) to create micro-patterns. The interfacial stresses, however, can also be generated by a tangential electric field (Roberts 2009;Melcher 1974). Using an electric field parallel to an air/polystyrene interface, Salac et al (2004) obtained randomly distributed islands with different sizes on the surface of a polystyrene film.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…But the effects of the lateral electrical force can be very significant in some situations . However, it can become a complex problem when both the normal and tangential electric fields are considered (Roberts 2009). Also, theoretical analysis showed that chemically heterogeneous and patterned substrates could also be used to induce a spatial electric field distribution to obtain the desired pillar array (Srivastava et al 2010;Atta et al 2011).…”
Section: List Of Symbolsmentioning
confidence: 99%
“…The presence of an electric field close to a liquid polymer surface has been demonstrated to induce instabilities of the polymer-air interface and thereby control the morphology of the surface (Schaffer et al 2000(Schaffer et al , 2001Salac et al 2004;Lin et al 2002;Marariu et al 2002;Atta et al 2011). The resulting electrostatic induced deformation method has been developed to realize the microand nanofabrication of features in polymeric materials (Schaffer et al 2000(Schaffer et al , 2001Salac et al 2004;Lin et al 2002;Marariu et al 2002;Wu and Russel 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Morariu et al described electric field‐induced structure formation in a bilayer polymer layer due to electrohydrodynamic instabilities produced by the application of in‐plane field . David Salac et al also reported the formation of self‐assembled patterns on polymer layer by an in‐plane electric field using two parallel electrodes with air gap . Oleksiy Lyutakov et al created micro‐sized patterns on polymethyl methacrylate (PMMA) polymer thin films by the effect of external field applied perpendicular to the film surface.…”
Section: Introductionmentioning
confidence: 99%
“…[5] David Salac et al also reported the formation of self-assembled patterns on polymer layer by an in-plane electric field using two parallel electrodes with air gap. [6] Oleksiy Lyutakov et al created micro-sized patterns on polymethyl methacrylate (PMMA) polymer thin films by the effect of external field applied perpendicular to the film surface. In their work, the PMMA film prepared by spin-coating onto Si wafer was subjected to the perpendicular electric field created by a strip electrode.…”
Section: Introductionmentioning
confidence: 99%